Pengaruh Desain dan Inovasi Produk Terhadap Kepuasan Konsumen dan Dampaknya pada Loyalitas Konsumen (Studi Kasus pada Konsumen Lipstik Wardah Kosmetik Jabodetabek) - Melani Quintania; Sasmitha Sasmitha (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
This study aims to determine the effect of the design, product innovation on consumer satisfaction and its impact on consumer loyalty to Wardah cosmetic lipstick products in region of Jabodetabek. This research is an explanatory type of research that uses a quantitative approach in the form of observation. The results use primary data in the way of surveys to consumers. Sampling determines using conditions for consumers, namely at least three purchases in the last five months, 17 years old, and can understand and fill out the questionnaire applied to obtain a final sample of 200 respondents. The data analysis method uses path analysis and uses the SPSS (Statistical Package for The Social Science) program. The results of this study prove that product design and innovation have a positive and significant effect on customer satisfaction and customer satisfaction has a positive and significant impact on customer loyalty. Product design and innovation have a direct influence on consumer loyalty while not having a substantial effect on consumer loyalty through customer satisfaction.